2003
DOI: 10.1016/s0921-5093(02)00592-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of melt convection and solid transport on macrosegregation and grain structure in equiaxed Al–Cu alloys

Abstract: Macrosegregation in metal casting can be caused by thermal and solutal melt convection, and the transport of unattached solid crystals. These free grains can be a result of, for example, nucleation in the bulk liquid or dendrite fragmentation. In an effort to develop a comprehensive numerical model for the casting of alloys, an experimental study has been conducted to generate benchmark data with which such a solidification model could be tested. The specific goal of the experiments was to examine equiaxed sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 20 publications
2
12
0
Order By: Relevance
“…This finding is also in agreement with the new predictor. Similar bottom-cooled directional solidification experiments on Al-1%Cu and Al-10%Cu, carried out by Rerko et al, 29) showed that, in the absence of grain refiners, the dilute alloy was completely columnar, the concentrated alloy completely equiaxed. Previously, Griffiths et al had also noted 30) that the size of the equiaxed zone increased with nominal Cu concentration in a series of Al-Cu alloy ingots solidified vertically downwards in order to promote convection in the bulk liquid.…”
Section: Comparison Of Predictions With Experimentssupporting
confidence: 62%
“…This finding is also in agreement with the new predictor. Similar bottom-cooled directional solidification experiments on Al-1%Cu and Al-10%Cu, carried out by Rerko et al, 29) showed that, in the absence of grain refiners, the dilute alloy was completely columnar, the concentrated alloy completely equiaxed. Previously, Griffiths et al had also noted 30) that the size of the equiaxed zone increased with nominal Cu concentration in a series of Al-Cu alloy ingots solidified vertically downwards in order to promote convection in the bulk liquid.…”
Section: Comparison Of Predictions With Experimentssupporting
confidence: 62%
“…The influence of the fluid flow in the solidification process on the solidification microstructure has aroused extensive interest in the field of material physics [1][2][3]. The basic effect of the fluid flow is to change the solute distribution and the heat transfer condition at the front of solid-liquid interface.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases experimentally examined, the solute was denser than the solvent, thus inducing a denser solute-enriched melt in the mushy zone and ahead of the growth interface. Under these conditions, it is expected that no natural convection occurs, since both the temperature and compositional gradients have a stabilizing effect on the density stratification [14][15][16].…”
Section: Introductionmentioning
confidence: 99%